2009
DOI: 10.1007/s00421-009-1079-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of endurance training on changes in purine metabolism: a longitudinal study of competitive long-distance runners

Abstract: The purpose of the study was to characterize the changes in purine metabolism in long-distance runners in the main phases of their 1-year training cycle. Nine male athletes competing in distances 5 and 10 km at national/regional level, mean age 22.9 +/- 0.6 years, practising sport for 8.6 +/- 0.3 years, participated in the study. The changes in plasma concentrations of hypoxanthine (Hx), xanthine (X) and uric acid (UA) and the activity of the enzyme HGPRT in red blood cells haemolysate were followed in four ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 30 publications
9
22
0
Order By: Relevance
“…To our knowledge, HGPRT postexercise activity has not been studied as of yet. The values obtained in this study are very similar to our previous research (40) and comparable with those revealed by other authors in healthy nontrained controls at rest, where HGPRT activity ranged between 70 and 160 nmol-mg"'-h"' (7,19,36) In a research of Stolk et al (33), a tendency, although not significant. toward increasing activity of HGPRT with age has been revealed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To our knowledge, HGPRT postexercise activity has not been studied as of yet. The values obtained in this study are very similar to our previous research (40) and comparable with those revealed by other authors in healthy nontrained controls at rest, where HGPRT activity ranged between 70 and 160 nmol-mg"'-h"' (7,19,36) In a research of Stolk et al (33), a tendency, although not significant. toward increasing activity of HGPRT with age has been revealed.…”
Section: Discussionsupporting
confidence: 93%
“…Purine metabolism has not yet been described in competitive athletes in a long-lasting training cycle, except for our previous attempt with long-distance runners (40). However, the effect of training loads was not analyzed there in detail.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it can be noted that higher HGPRT activity after high intensity training in which the dominant energy is anaerobic is an indicator of a better salvage pathway for reconstruction of adenine purine nucleotides (6). An increase in HGPRT after training has also been previously reported (9,15,25). It has also been indicated that in 4 seasons of the annual training cycle (adopted from Bompa, 1999), the match season in which the training moved towards anaerobic, the relaxing activity of this enzyme was high, and this is consistent with the findings of the present study because HIIT activities in which the major energy system is anaerobic can increase this enzyme and as a result, improve the salvage pathway purine nucleotides (26).…”
Section: Discussionmentioning
confidence: 71%
“…It has been reported that high hypoxanthine is the result of overtraining (15) and its concentration depends on the intensity of sport (16). In extreme speed sport, hypoxanthine can be 40 times higher than its resting values (17).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, training modality or type of physical activity are surely of great importance. Although training data were not collected here in detail, training profiles of young and older speed-power and endurance athletes are clearly distinct (9,20,40). It seems that the combination of regular aerobic and high-intensity anaerobic exercise brings about an increased level of threshold parameters in SP, far above the capabilities of untrained subjects, across the whole age range analyzed.…”
Section: Discussionmentioning
confidence: 80%